KEMUDAHAN INVESTOR DALAM PROSES INVESTASI MODAL ASING DI BANTEN - Rina Yulianti (Jurnal Administrasi Publik, 2015)
Investment is the investment made by local and international companies.And Banten is one area that many ogled for investment, so Banten had to do a lot ofpreparation to provide convenience services. With the increase in the area of investmentwill be realized if there is a potential area that can be "sold" to investors, whether it benatural resources and potential of human resources. The next thing that is veryimportant is the ability to sell potential. The ability to sell must be supported by thecreation of a conducive environment and support areas such as investment; theguarantee of security and legal certainty for investment, as well as excellent publicservice delivery. If Banten wants advanced economies, the economy must alwaysimprove to increase capital investment and quality of human resources, and increaseprosperity and create jobs. This research approach using qualitative methods. Banten isan area with a fairly high industrial growth, thus making parties interested in investing.The results showed that with ease in providing one-stop service and not a lot ofbureaucracy that is passed so as to make investors happy. This is certainly an impact oninvestment into Banten. So as to increase rather than the economy Banten, andabsorption of human resources in the field of work.